Bilayers of Ni3C12S12 and Pt3C12S12: graphene-like 2D topological insulators tunable by electric fields. (20th October 2017) - Silveira, Orlando J; Lima, Érika N; Chacham, Hélio
Abstract: In the present work we predict, through first-principles calculations, that bilayers of the recently synthesized Ni3 C 12 S 12 and Pt3 C 12 S 12 layered materials are topological insulators upon electron doping, and that their topological insulator properties can be modulated by the application of electric fields with magnitudes achievable in devices. The electronic structures of both bilayers are characterized by spin–orbit split graphene-like bands, with gap magnitudes that are three orders of magnitude larger than graphene's. In ribbon geometries, chiral edge modes develop at each side with band dispersions similar to that of Kane–Mele graphene model. Surprisingly, the edge states' spin-propagation locking occurs even for very thin ribbons. We also find that the response of the electronic structure of both materials to applied electric fields are similar to both graphene and the Kane–Mele model with a Rashba term. All these findings indicate that these bilayer systems can be considered as large-spin–orbit graphene analogues with a strong sensitivity to applied electric fields.